The Effect of Collaborative Project-Based Learning on Students’ Communication Skills at SMP Negeri 4 Palu - Sunarti, Dwi Ninik; Bialangi, Mursito S.; Masrianih; Alibasyah, Lestari M.P.; Agni, Raya; Astija (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of collaborative project-based learning (PjBL) on students’ communication skills at SMP Negeri 4 Palu. A quasi-experimental nonequivalent control group design was employed, involving 22 students in the experimental group and 24 students in the control group selected through cluster random sampling. The intervention was implemented through a contextual project, the Eco-Soil Poster Campaign, which involved creating a digital poster campaign promoting soil health conservation within the school environment. Data were collected using a posttest communication skills questionnaire, while a cognitive pretest was administered to verify the initial equivalence of the two groups. The instrument was validated using Aiken’s V and Cronbach’s Alpha. The results revealed a significant difference between the two groups (p = 0.018 < 0.05), with the experimental group achieving a higher mean score (75.64%, categorized as Good) than the control group (69.83%, categorized as Fair), accompanied by a moderate effect size (Cohen’s d = 0.724). These findings indicate that collaborative PjBL significantly improves students’ communication skills and can be recommended as an effective instructional strategy for junior high school biology learning.